Identifying the Components of a Personal Development Program Model Based on Workplace Learning in the Educational System - Hadian, Seyedeh Zahra; Salimi, Ladan; Fallah, Vahid (Assessment and Practice in Educational Sciences, 2025)
This study aimed to identify the key components of a personal development program model based on workplace learning within the educational system. Employing a qualitative research design, the study utilized semi-structured interviews with 13 purposefully selected educational experts, including curriculum specialists and professionals affiliated with the Ministry of Education. Participants were chosen through purposive sampling and interviews continued until theoretical saturation was achieved. The data collection process was supported by document analysis involving scholarly articles, reports, and educational policy documents. Thematic analysis was carried out through qualitative content analysis using open, axial, and selective coding to extract meaning units, categorize concepts, and develop a comprehensive model. The validity of findings was enhanced through triangulation with expert opinions and theoretical literature in the field. Analysis of the interviews led to the identification of ten main components essential for personal development through workplace learning: problem-solving skills, job knowledge, creativity, innovation and ideation, critical thinking, achievement motivation, team spirit, communication skills, resilience, and learning motivation. These components were derived from 40 open codes extracted from expert responses. The findings confirmed that workplace learning contributes to the development of both cognitive and socio-emotional competencies. The presence of contextual learning opportunities in professional environments fosters continuous improvement, reflective practice, and collaborative growth among educators. The study presents a theoretically grounded and contextually validated model of personal development tailored to the educational system. The findings emphasize the need for educational institutions to integrate development programs within authentic workplace settings, prioritizing holistic competency-building over isolated training activities. This model has practical implications for policy design, teacher training, and institutional leadership seeking to enhance professional growth through workplace-embedded strategies.